The Impact of Spiritual Leadership on Organizational Citizenship Behavior: A Multi-Sample Analysis - Chen, Chin-Yi; Yang, Chin-Fang (2012)
This study investigates and compares the impact of spiritual leadership on organizational citizenship behavior in finance and retail service industries to determine the possibility of generalizing and applying spiritual leadership to other industries. This study used multi-sample analysis of structural equation modeling. The results show that values, attitudes, and behaviors of leaders have positive effects on meaning/calling and membership of the employees, and further facilitate employees to perform excellent organizational citizenship behaviors, including the altruism of assisting colleagues and the responsible conscientiousness toward organization. The effect of altruism toward colleagues is especially stronger. Finally, the effect of leaders’ values, attitudes, and behaviors on the spiritual survival of employees is stronger in retail than that in finance.
Keywords: Retail industry; Finance industry; Multi-sample analysis; Organizational Citizenship Behavior; spiritual leadership